Total organic carbon in pond waters from the Labyrinth of southern Victoria Land in the Antarctic - Genki I. Matsumoto; Kunihiko Watanuki; Tetsuya Torii (National Institute of Polar Research, 1987)
Total organic carbon (TOC) in 10 freshwater and saline ponds in the Labyrinth (77°33′S, 160°50′E) of southern Victoria Land, Antarctica, was preliminary studied to clarify their distribution and sources. The TOC concentrations ranged from 0.78 to 23.1mgC/l. The high TOC concentrations were found only in saline pond waters. The correlation coefficient between electric conductivity and TOC value was considerably high (0.82). This result can be explained as follows : Organic substances supplied from snow and glacial meltwaters are first concentrated in the residual pond waters by freezing out. Also in situ photosynthetic activity produces organic substances, but certain labile organic constituents may be degraded by microbial activity. Further, repeating freezing and evaporation of pond waters work to concentrate relatively refractory organic substances in the pond bottom waters, together with dissolved inorganic salts over a long period of time.